2023
DOI: 10.24018/ejbmr.2023.8.1.1766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of E-Service Quality on E-Repurchase Intention in Indonesia Online Shopping: E-Satisfaction and E-Trust as Mediation Variables

Abstract: The purpose of this study is to develop new knowledge in understanding the effect of electronic service quality on customer satisfaction, customer trust and customer purchase intention and to understand the mediating role of customer satisfaction and customer trust in the relationship between service quality and purchase intention in online shopping in Indonesia. The result is expected to be a better strategy in developing service quality electronically which has an impact on customer behavior. This study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
5
3
0
Order By: Relevance
“…Trust has a very important role in online business because online shopping has a bigger risk than offline shopping, so the quality of a website will be very influential. This is also in line with several studies related to e-commerce which found that e-service quality affects customer trust (Cahyono, 2015;Purnamasari, 2018;Susanti et al 2018;Wijaya et al 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Trust has a very important role in online business because online shopping has a bigger risk than offline shopping, so the quality of a website will be very influential. This is also in line with several studies related to e-commerce which found that e-service quality affects customer trust (Cahyono, 2015;Purnamasari, 2018;Susanti et al 2018;Wijaya et al 2018).…”
Section: Introductionsupporting
confidence: 86%
“…Al-dweeri, Ruiz Moreno, Montes, Obeidat, and Al-dwairi (2019) stated that satisfaction could operate as a mediator between website quality and client loyalty because if the service quality is not good, the customer will not be loyal. The same conclusion was reached by Purnamasari (2018), Wibowo and Wahid (2019), and also Giao et al (2020) that Customer satisfaction serves as a bridge between website quality and consumer loyalty in E-commerce.…”
Section: The Mediating Role Of E-satisfactionsupporting
confidence: 63%
“…The involvement of this mediating variable is consistent with earlier research. For instance, Al-dweeri et al (2019), Purnamasari (2018), Wibowo andWahid (2019), andGiao et al (2020) explain that customer satisfaction acts as a mediator between website quality and customer loyalty in E-commerce since if the service quality is not adequate, the client will not be loyal. E-satisfaction does not mediate between the effect of the payment system and electronic loyalty, as indicated by mediation tests.…”
Section: The Mediating Effect Of E-satisfaction On Web-quality Paymen...mentioning
confidence: 99%
See 1 more Smart Citation
“…This can happen if an attractive and very eye-catching design can attract consumers to make repeat purchases online. These results are supported byIqbal & Tantra (2023) andPurnamasari & Suryandari (2023) who state that Website Design Quality has a positive and significant effect on Repurchase Intention. However, different from the results of previous research, the results of research from Aurelia & Nawawi (2021) andAufa & Marsasi (2023) show that Web Design Quality has no effect on Repurchase Intention.…”
supporting
confidence: 58%